STUDY OF APPLICATION "BATIK" IN THE INTERIOR OFFICE PARTITION - Tunjung Atmadi Suroso Putro; Rizky Dinata; Ali Ramadhan (Journal of Urban Society's Arts, 2019)
Office partitions are part of office furniture that serves as a dividers of office space. Office partitions provide solutions to organize work space in the office to make it more tidy and efficient. The use of office partition is a modern concept of office space in maximizing office space to make it more comfortable. By applying knock down system to the office partition, wall panels can be dismantled and installed back to be installed or applied with certain batik pattern. The office interior now became an important part to represent clients to increase the look of an office. The method used in this research is descriptive qualitative method, starting from the initial concept of the product, product development and prototype application of batik motif design on the partition. The results of this study are expected to be able to complement the space image with a certain style as a supporting element of interior design, as well as add to the appearance of the office interior to be more dynamic and increase working productivity.